Detailed profiling on DNA binding affinity, cytotoxicity and pathway of induced cell death of novel water-soluble Cu(Ⅱ)-based acylhydrazone porphyrin derivatives. (January 2017) - Feng, Xiao-Xia; Zhang, Jun-Xiang; Wu, Yu; Zhang, Qian; Liu, Jia-Cheng
Abstract: A panel of novel water-soluble Cu(Ⅱ)-based acylhydrazone porphyrin complexes (denoted asCu-PorX, X  = 1, 2 and3 . See Fig. 1) were prepared and characterized. Versatile physicochemical approaches indicated that whole compounds could effectively bind with ct-DNA through intercalative or intercalative coupled with end-stacking interaction, especially, Cu-Por3 has the strongest binding affinity compared with others. Additionally, the antiproliferative activity has been evaluated by MTT assay turned out that Cu-Por3 yet exhibits gratifying cytotoxicity towards A549 (non-small cell lung cancer) cell line, suggesting that Cu-Por3 is a potential candidacy among tested agents. We also carried out the cellular uptake measurement by using an extracted method to better comprehend the anticancer behaviors. Moreover, for gaining deeper insight into the mechanism of cell death of affected by the representative complex Cu-Por3, the influences of this new conjugate on the cell cycle and the induction of apoptosis were illustrated via employing flow cytometric analysis. Graphical abstract: Novel water-soluble Cu(Ⅱ)-based acylhydrazone porphyrin derivatives have been synthesized. Versatile physicochemical approaches indicated that all the complexes could effectually bind with ct-DNA via intercalative or end-stacking interactions, especially, Cu-Por3 has the strongest binding affinity compared with others. Meanwhile, the antiproliferative activity has been evaluated by MTT assay turned out that Cu-Por3 yet exhibits gratifying cytotoxicity in A549 human lung cancer cell lines, suggesting that Cu-Por3 is a potential candidacy among the tested agents. An extraction method was performed to quantified identify the cellular uptake to better comprehend the anticancer behaviors. Moreover, the mode of cell death effected by the representative Cu-Por3 complex has been explored by using various biochemical techniques like cell cycle and apoptosis through flow cytometric analysis. Highlights: Three novel Cu(Ⅱ)-based acylhydrazone porphyrin derivatives have been synthesized. Versatile physicochemical means suggested Cu-Por3 has strongest binding affinity. MTT tests showed Cu-Por3 with good cytotoxicity to A549, but weak for normal cell. An extraction method was performed to quantified identify the cellular uptake. Besides, Cu-Por3 induced A549 death mainly via apoptotic and arrested G1 phase.